Rasionalisme Rene Descartes - Choiriyah, Ngismatul (Anterior Jurnal, 2018)
Rasionalisme is assumption where mind is the only resource to overcome truth which is beyond sense. Rene Descarates found method to make realistic philosophic and logic by doubtful everyting or implementing doubtful method which mean doubtful should include all informations we have. According to Descartes mind is the stand-alone substance in term I think I exist, mind is immaterial. Mind is conscious and its character is to think and body is part of matery. Matery character is immensity.